Capital raising in the offshore market - Aggarwal, Reena; Gray, Ian; Singer, Hal (Journal of Banking & Finance, 1999)
US corporations can raise capital in the offshore market using Regulation S, adopted by the Securities and Exchange Commission (SEC) in 1990 and modified in 1996. We examine how offshore offerings are done under Regulation S, what types of companies use this market, the discount companies offer investors to compensate for illiquidity in the market, and the impact of the new disclosure requirements on capital raising in the offshore market. We find that small firms tend to raise capital in this market. During our sample period before the 1996 rule change the median market capitalization of reporting firms was $16.82 million with a median stock price of $1.13. The mean and median discount offered to foreign investors was 32.84% and 40.53%, respectively. Offerings during this period resulted in average share dilution of 11.97%. We find that before the disclosure requirements, firms were “gaming the system” by giving foreign investors just enough time to resell the securities back into the United States before the initial sale became public information. After the rule changes, Regulation S offerings are not perceived to be “shady”, and larger firms are now using the market, resulting in lower average discount and dilution.